1997
DOI: 10.1111/j.1365-2222.1997.tb01159.x
|View full text |Cite
|
Sign up to set email alerts
|

Malnutrition and experimental lung allergy

Abstract: These results suggest that the capacity to release inflammatory mediators and the vascular response to these mediators is not affected by this type of malnutrition and, therefore, the diminished response of the airways reported here is probably due to the lower levels of anaphylactic antibodies produced by the malnourished rats.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…A low protein diet in balb/c mice reduces the skin responses to a histamine liberator [149], histamine [149] and allergens [150]. Defects in humoral immunity have also been shown in mice following both acute [151] and chronic starvation [152], and rat studies have shown a reduction in IgE binding sites on mast cells [153], reduction in IgE and inhibition of anaphylaxis in the lungs of sensitized animals [154], and reduction in IL‐4 and mast cells [155] when nutritional intake was reduced. Conversely, several pro‐inflammatory cytokines and mediators including IL‐6 and TNF‐α are associated with increased adipose tissue [156].…”
Section: Foods Nutrients and Allergic Diseasementioning
confidence: 99%
“…A low protein diet in balb/c mice reduces the skin responses to a histamine liberator [149], histamine [149] and allergens [150]. Defects in humoral immunity have also been shown in mice following both acute [151] and chronic starvation [152], and rat studies have shown a reduction in IgE binding sites on mast cells [153], reduction in IgE and inhibition of anaphylaxis in the lungs of sensitized animals [154], and reduction in IL‐4 and mast cells [155] when nutritional intake was reduced. Conversely, several pro‐inflammatory cytokines and mediators including IL‐6 and TNF‐α are associated with increased adipose tissue [156].…”
Section: Foods Nutrients and Allergic Diseasementioning
confidence: 99%